2007
DOI: 10.1080/09588220601118487
|View full text |Cite
|
Sign up to set email alerts
|

Learning to orchestrate online instructional conversations: A case of faculty development for foreign language educators

Abstract: In the past decade, providing language instruction via computer-mediated communication (CMC) has seen tremendous growth throughout the world. With this increase in asynchronous instruction have come questions concerning the role of the instructor as it determines the quality and impact of learning and of what optimal faculty development might consist. This study addresses the question: Can simulated instructional conversations using CMC be used effectively in faculty professional development? An online profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
(6 reference statements)
2
20
0
Order By: Relevance
“…In addition, language teaching supported by synchronous communication tools seems to foster a particular type of pedagogy -that of ''instructional conversation'' (cf. Moore & Kearsley, 2005;Meskill & Anthony, 2007;Guichon & Drissi, 2008), whereby most of the learning takes place during oral interaction that alternates formal moments during which the stress is put on carrying out learning tasks and informal moments favorable to the development of intercultural and conversational skills. Instructional conversation, seen as a loosely structured communicative activity, could thus be a means to get learners to negotiate the meaning of a message in L2 and develop their interlanguage, thanks to the mediation of an expert.…”
Section: N Guichonmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, language teaching supported by synchronous communication tools seems to foster a particular type of pedagogy -that of ''instructional conversation'' (cf. Moore & Kearsley, 2005;Meskill & Anthony, 2007;Guichon & Drissi, 2008), whereby most of the learning takes place during oral interaction that alternates formal moments during which the stress is put on carrying out learning tasks and informal moments favorable to the development of intercultural and conversational skills. Instructional conversation, seen as a loosely structured communicative activity, could thus be a means to get learners to negotiate the meaning of a message in L2 and develop their interlanguage, thanks to the mediation of an expert.…”
Section: N Guichonmentioning
confidence: 96%
“…This view of learning is in keeping with Long's (1990) Interaction Hypothesis that contends that L2 acquisition is facilitated when (1) interactions give rise to negotiations and result in comprehensible output (Swain, 2000), when (2) feedback is provided to learners, and when (3) learners are incited to recast their own utterances by their interlocutors. Let us underscore that, contrary to other disciplines, foreign language is both the aim and the means of instruction, that is to say it is co-produced in real-time by collaborative actions (Raymond et al, 2005) and the outcome of this collaboration also makes up the content ''with which the learner's mind interacts and consequently learns'' (Meskill & Anthony, 2007).…”
Section: N Guichonmentioning
confidence: 98%
“…Changes in practice and underlying beliefs will be incremental; it is unrealistic to expect rapid changes. Meskill and Anthony (2007) found that a workshop improved professors' ability to engage in effective online instructional conversations. This is certainly an indication that others could benefit from gaining experience in conducting and promoting instructional conversations.…”
Section: Modifying Teaching Approaches and Beliefsmentioning
confidence: 99%
“…Given that faculty members are subject matter experts in the classroom, without professional development, they may not be creating the most effective learning environments for students (Meskill & Anthony, 2007). As institutions adopt online education to support institutional growth and student needs, it becomes essential to provide faculty with effective professional development opportunities that expose them to online methodologies (Vaill & Testori, 2012).…”
Section: Best Practices Framework For Online Faculty Professional Devmentioning
confidence: 99%